2016
DOI: 10.12806/v15/i3/r2
|View full text |Cite
|
Sign up to set email alerts
|

Experiences and outcomes of a women’s leadershipdevelopment program: A phenomenological investigation

Abstract: This application brief provides pedagogical strategies for teaching and learning about women and leadership as a potentially sensitive subject, with emphasis on creating an intellectually safe learning environment. Findings from a study of students' expectations and experiences with a Women and Leadership course showed that the strategies affected students' learning experiences. Some strategies also challenged the instructor as a woman leader.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 60 publications
0
27
0
Order By: Relevance
“…The participants from the treatment group were also concerned with the clarity of the leadership program's mission, vision, objectives, and enforcing values, supporting the results of Allio (2005) and Trinidad and Normore (2005). Additionally, Krystal and Brue (2016) highlighted that providing experiential learning and network development are essential for leadership program success. The results also agreed with Debebe (2011) who asserted that learning from the shared experiences of female leaders in a safe environment to internalize confidence for successful leaders is an important factor for leadership programs success.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The participants from the treatment group were also concerned with the clarity of the leadership program's mission, vision, objectives, and enforcing values, supporting the results of Allio (2005) and Trinidad and Normore (2005). Additionally, Krystal and Brue (2016) highlighted that providing experiential learning and network development are essential for leadership program success. The results also agreed with Debebe (2011) who asserted that learning from the shared experiences of female leaders in a safe environment to internalize confidence for successful leaders is an important factor for leadership programs success.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, administrative creativity is greatly influenced by psychological empowerment for academic female leaders. Likewise, Krystal and Brue (2016) conducted a study using the phenomenological method to explore the experiences of 7 alumni of a "women's-only" leadership program. Through semi-structured interviews, the authors found that the learning elements were the most beneficial in enhancing individuals' leadership role.…”
Section: Barriers To Leadershipmentioning
confidence: 99%
“…Leadership learning has been shown to transfer from leadership development training for working professionals into the work environment (Brue & Brue, 2016;Coloma et al, 2012;Patton et al, 2103), and some evidence exists that leadership learning can effectively transfer from a structured undergraduate leadership program into the workplace (Mitchell & Daugherty, 2019;Soesbe, 2012 learning displayed results in which students learned more about themselves or became more confident as leaders (Bond & Sterrett, 2014;Chesnut & Tran-Johnson, 2013;Eich, 2008;Soesbe, 2012). Alumni of an undergraduate leadership program at a liberal arts institution believed the strengths assessment and other similar assessments led to greater selfawareness and a better understanding of the way they lead others (Soesbe, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…A Structuralists perspective assumes that social pressures and expectations provide a normative regulation of roles; this type of role taking asks persons to internalize the systems of behaviors typically prescribed for that role (Ebaugh, 1988;Nye, 1976). Previous studies (Brue & Brue, 2016;Ely et al, 2011;Ely & Meyerson, 2000;Gherardi & Poggio, 2001) provide insight into the experiences of emerging woman leaders regarding this structural role taking process during and after WOLD program participation.…”
Section: Role Assumptionmentioning
confidence: 99%